2022
DOI: 10.1016/j.jiac.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Duration of infectious virus shedding in patients with severe coronavirus disease 2019 who required mechanical ventilation

Abstract: Background: Approximately 5% of patients with coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 develop severe COVID-19. Severe COVID-19 requires respiratory management with mechanical ventilation and an extended period of treatment. Prolonged infectious virus shedding is a concern in severe COVID-19 cases, but few reports have examined the duration of infectious virus shedding. Therefore, we investigated the duration of infectious virus shedding in patients transferred t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…Viral RNA excretion for MV may remain detectable based on RT-PCR testing for long periods of time, even after viable virus is no longer detected [23,26]. A similar is reported with SARS-CoV-2 in people where COVID-19 patients stop shedding infectious virus early in the course of the disease but remain positive on RT-PCR testing for a much longer period [27,28].…”
Section: Plos Onesupporting
confidence: 52%
“…Viral RNA excretion for MV may remain detectable based on RT-PCR testing for long periods of time, even after viable virus is no longer detected [23,26]. A similar is reported with SARS-CoV-2 in people where COVID-19 patients stop shedding infectious virus early in the course of the disease but remain positive on RT-PCR testing for a much longer period [27,28].…”
Section: Plos Onesupporting
confidence: 52%
“…In addition, it was suggested that viral clearance may be reduced and viruses may be shed for a longer period in patients with severe disease (23). Reports of severe and immunocompromised patients in Japan suggested that infectious viruses may be shed for a period of nearly 3 weeks (24). The CDC recommends an isolation duration of about 3 weeks for severe COVID-19 patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Vero cells expressing TMPRSS2 (VeroE6/TMPRSS2 cells, JCRB1819; JCRB Cell Bank, Japan) were used to culture SARS-CoV-2. The viral culture method used was similar to that described previously [ 10 ]. The cells were observed for 5 days to check for cytopathic effects (CPEs), and the infection titer was determined using the TCID 50 method.…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR was performed as described previously [ 10 ]. Nucleic acid extraction of SARS-CoV-2 was performed using the Maxwell® Viral Total Nucleic Acid Purification Kit (Promega Corporation, Madison, WI, USA), and RT-qPCR was performed using the One Step PrimeScript™ III RT-qPCR mix (Takara Bio Inc., Japan).…”
Section: Methodsmentioning
confidence: 99%